Challenges in the development and growth of small for gestational age newborns. Issue 4 (4th July 2017) - Iughetti, Lorenzo; Lucaccioni, Laura; Ferrari, Fabrizio
ABSTRACT: Introduction : Being born with low birth weight (less than 2.500 gr) is considered a public health problem, with an overall world rate of about 14%. Low birth weight may result from a premature birth (< 37 weeks of gestation), from several causes of intra-uterine growth restriction or from a combination of both. Areas covered : We described how, if weight and/or length at birth are not adequate for gestational age, the newborn is considered 'small for gestational age' and may present several growth, hormonal and developmental peculiarities, possibly due to the growth restriction developed during pregnancy. Expert commentary : We provide a description of the possible mid-term consequences of being born small for gestational age and how to follow and provide care for these babies from a multidisciplinary point of view.